Nanocone-based plasmonic metamaterials. (6th December 2018) - Córdova-Castro, R Margoth; Krasavin, Alexey V; Nasir, Mazhar E; Zayats, Anatoly V; Dickson, Wayne
Abstract: Metamaterials and metasurfaces provide unprecedented opportunities for designing light–matter interactions. Optical properties of hyperbolic metamaterials with meta-atoms based on plasmonic nanorods, important in nonlinear optics, sensing and spontaneous emission control, can be tuned by varying geometrical sizes and arrangement of the meta-atoms. At the same time the role of the shape of the meta-atoms forming the array has not been studied. We present the fabrication and optical characterization of metamaterials based on arrays of plasmonic nanocones closely packed at the subwavelength scale. The plasmonic mode structure of the individual nanocones and pronounced coupling effects between them provide multiple degrees of freedom to engineer both the field enhancement and the optical properties of the resulting metamaterials. The metamaterials are fabricated using a scalable manufacturing procedure, allowing mass-production at the centimeter scale. The ultra-sharp cone apex ( ≲ 2 nm) and the associated field enhancement provide an extremely high density of electromagnetic hot-spots (∼10 10 cm −2 ). These properties of nanocone-based metamaterials are important for the development of gradient-index metamaterials and in numerous applications in fluorescence enhancement, surface enhanced Raman spectroscopy as well as hot-carrier plasmonics and photocatalysis.